Terrasses aux mosaïques de Choqek’iraw, Pérou. Description générale et premières interprétations - Patrice Lecoq (Journal de la Société des Américanistes)
The mosaic-adorned terraces of the Inca site of Choqek’iraw, Peru. General description and some elements for their interpretation. Choqek’iraw, in the heart of the Vilcabamba cordillera, in Peru, some 150 km from the ancient Inca State capital Cuzco, is one of the very few Pre-Hispanic sites displaying large wall mosaics, and the only one known from Inca times. This paper will attempt to demonstrate that the figures represented on the walls convey cosmological significance and are laid out following textile principles. We will first describe the site and its geo-cultural setting. Then, the mosaics’ main characteristics will be examined in detail, in attempt to grasp their meaning. We conclude this paper by suggesting that some of the scenes depicted might have been inspired by pre-Columbian myths and might be linked to astronomical concepts.